Image quality as a possible method of in situ monitoring the in-vessel mirrors - Konovalov, V.G.; Makhov, M.N.; Shapoval, A.N.; Ashikawa, N.; Masuzaki, S.; Sagara, A.; Naidenkova, D.I.; Ryzhkov, I.V.; Shtan, A.F.; Solodovchenko, S.I.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2006)
The plasma facing mirrors (FM) in ITER will be subjected to sputtering and / or contamination with the rates depending on mirror locations. The result of influence of both these factors will be reduce of mirror reflectance (R) and worsen the quality of transmitted image (IQ). This implies that control of the mirror quality in- situ is an actual problem, and this work is an attempt to approach to its solution. The method suggested for evaluation of IQ was applied to mirrors exposed in LHD, TRIAM-1M, TS and in the DSM-2 stand (IPP NSC KIPT).